Students’ Views of Classroom Debates as a Strategy to Enhance Critical Thinking and Oral Communication Skills - Nurakhir, Asih; Nindya Palupi, Fiqih; Langeveld, Cornelia; Nurmalia, Devi (Nurse Media Journal of Nursing, 2020)
Background: The skills in effective communication and critical thinking are essential for nurses to apply appropriate judgments in the delivery of patient care. Classroom debates are evident to be an effective strategy that can be used to improve such skills. Unfortunately, research focusing on classroom debates to promote critical thinking and oral communication skills among nursing students has not been extensively explored.   Purpose: This study aimed to explore nursing students’ views of classroom debates as a learning strategy to enhance critical thinking and oral communication skills.Methods: A descriptive qualitative research design was employed in this study. Twelve students of the undergraduate program in nursing with classroom debate experiences and willingness to participate were purposively recruited for semi-structured interviews. Open-ended questions were used, and probing questions were also generated from the participants to get more detailed information. The interviews were transcribed verbatim and analyzed using the inductive content analysis. Results: The results of the study identified five themes, including the acquisition of new knowledge, awareness and responsiveness to diverse viewpoints and arguments, learning structuring ideas and appropriate ways of presentation, development of other necessary skills, and challenges of classroom debates in nursing education.  Conclusion: Classroom debates promoted the development of critical thinking and oral communication skills, and offered students an opportunity to develop other necessary skills in the face of today’s complex healthcare. Classroom debates can be integrated into the curriculum and teaching practices of any nursing educational institutions.